Avaliação de aspectos da estabilidade do arco e da geometria de pré-formas em manufatura aditiva utilizando o processo MIG/MAG CMT com foco na liga Ti-6Al-4V - Kovalenko, Oksana (2019)
This work had as main objective the evaluation of potential difficulties/limitations and ways of overcoming them in the wire and arc additive manufacture (WAAM), using CMT operating mode for the manufacture of the titanium alloy preforms. After preliminary tests, the operational behavior trends were determined in terms of the formation of layers due to variation of process parameters. Tests were done in stainless steel (plates and wire), using shielding gas Ar + 2% O2. The adjustment parameters arc length correction and boost corrections have influence on more than one of the parameters monitored, especially in the feeding speed and current, which makes difficult the geometry correction of the of the layer. During the use of the CMT mode for deposition of titanium alloy was observed a strong instability of the plasma jet. It was determined the effect of the shielding gas with different oxygen contents on the behavior of the arc. The tests were done in Ti-6Al-4V with electrode wire belonging to the class of the base material, using as protection gas Ar + O2 with different content of O2, in comparison with stainless steel. The behavior of the arc during deposition of titanium alloy proved to be very unstable for all tested gases. High-speed videos showed an intense consumption of oxides on the surface of the base material by the action of multiple cathodic points of the arc, which causes the need for frequent search for "fresh" oxides. In the case of deposition of stainless steel with higher content of O2 the stabilizing effect on the arc was obtained. Also, in order to control the geometry and heating of the preform during its deposition, a method of combining the MIG/MAG process with addition of cold wire was proposed. The study was made in carbon steel, using conventional MIG/MAG, and in titanium alloy, using MIG/MAG CMT. The method proved to be feasible for application in additive manufacture, offering an increase in the rate of deposition and reduction of the area affected by heat. For the titanium alloy it was noticed the reduction of the regularity of the preforms and the appearance of microcracks on the sides of the walls.